The Many Tunes of Perisomatic Targeting Interneurons in the Hippocampal Network - Ellender, Tommas J.; Paulsen, Ole (Frontiers in Cellular Neuroscience, 2010)
The axonal targets of perisomatic targeting interneurons make them ideally suited to synchronise excitatory neurons. As such they have been implicated in rhythm generation of network activity in many brain regions including the hippocampus. However, several recent publications indicate that their roles extend beyond that of rhythm generation. Firstly, it has been shown that, in addition to rhythm generation, GABAergic perisomatic inhibition also serves as a current generator contributing significantly to hippocampal oscillatory EEG signals. Furthermore, GABAergic interneurons have a hitherto unexpected role in the initiation of hippocampal population bursts, both in the developing and adult hippocampus. In this review, we describe these new observations in detail and discuss the implications they have for our understanding of the mechanisms underlying physiological and pathological hippocampal network activities. This review is part of the Frontiers in Cellular Neuroscience's special topic entitled GABA signalling in health and disease based on the meeting at the CNCR Amsterdam.